(untitled) (European Journal of Interdisciplinary Research and Development, 2022)
The problem with gypsum soils is that they have a high bearing capacity unless water reaches them. Nonetheless, it will create air spaces or cavities in these soils beneath the inundation states. It may collapse under the influence of the origin load and without additional external loads.